PENGETAHUAN PASIEN DIABETES MELITUS TENTANG DIET DM DI POLI DALAM RSUP DR. HASAN SADIKIN BANDUNG - Theresia Eriyani; Yulan Yuliana (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2019)
Background: Prevalence of diabetes mellitus in Garut about 6.11% with mortality reach 4.17%. DMORK sequences after stroke, CHF and pulmonary TB and will increase annually. Diet is the main therapy in DM, then every patient should have a positive attitude (support) to the diet so it can not happen. Where attitude is strongly related by knowledge. The purpose of this study was to determine the description of diabetes mellitus patients about the DM diet. This research was conducted in Poli Dalam RSUP Dr. Hasan Sadikin Bandung on 9-14 August 2012.Methods: The research method used is deskrptif and sample taken by chance, with the number of respondents as much as 25 people. Data completion technique using questionnaire.Results: Most respondents 52% information about Diet DM from doctors. In terms of economics, most respondents have health funds for treatment on a regular basis. Almost half of the respondents had DM <5 years. And almost half of the respondents were not active in finding information about the DM Diet. While the knowledge of respondents about Diet DM most have enough knowledge.